Revealing boarding room pricing practices during the covid-19 pandemic - Lilik Purwanti; Soelchan Arief Effendi; Aryo Prakoso; Sartika Fasta (Institute of Computer Science (IOCS), 2023)
Boarding houses are one of the needs for nomads, both workers or students from one region who are working or studying in other areas. At first, the boarding house business was considered a very promising business and had good prospects. The Covid-19 pandemic has had a tremendous impact on various aspects of life, including the boarding house business. This will have an impact on boarding room occupancy because students can take lectures online and can be done at their respective regional homes. This research is important to reveal how boarding house owners determine boarding room rentals during the pandemic. The study was conducted on boarding houses in the city of Malang located around a large campus with a concentration level of students. This research method uses qualitative methods, with an interpretive approach. Informants of boarding house owners and occupants are used to uncover the pricing of boarding room rents. The results showed that room rates were determined in various ways by calling fraternity prices, pandemic prices, and mutual aid prices. The fraternity price determines the rental price of a boarding room by looking at the ability of boarding house residents whose parents have been affected by the pandemic, for example not working anymore because they are laid off for an uncertain time. The estuary of price reductions and payment delays due to parents of residents of their business boarding houses being affected by the pandemic formed pandemic prices. The price of mutual assistance arises because boarding house residents do not occupy boarding rooms and only leave goods so that they only pay for electricity, wifi and water. The contribution of this research, especially to boarding house business actors specifically, as well as business people in general, in extraordinary conditions in the future can determine the price of mutual assistance and sympathy prices as a form of win win solutions.